Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1471-2334-11-254
|View full text |Cite
|
Sign up to set email alerts
|

High specificity of line-immunoassay based algorithms for recent HIV-1 infection independent of viral subtype and stage of disease

Abstract: BackgroundSerologic testing algorithms for recent HIV seroconversion (STARHS) provide important information for HIV surveillance. We have shown that a patient's antibody reaction in a confirmatory line immunoassay (INNO-LIATM HIV I/II Score, Innogenetics) provides information on the duration of infection. Here, we sought to further investigate the diagnostic specificity of various Inno-Lia algorithms and to identify factors affecting it.MethodsPlasma samples of 714 selected patients of the Swiss HIV Cohort Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 23 publications
(21 reference statements)
3
28
1
Order By: Relevance
“…In a recent study of patients known to have been infected for at least one year, we have demonstrated a high diagnostic specificity of the algorithms, which was not affected by the HIV-1 clade or the disease stage [36]. The present work also confirms the high specificity of the algorithms (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…In a recent study of patients known to have been infected for at least one year, we have demonstrated a high diagnostic specificity of the algorithms, which was not affected by the HIV-1 clade or the disease stage [36]. The present work also confirms the high specificity of the algorithms (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…Linking Inno-Lia based IIR estimation to the context of prospective, individual confirmation of an HIV diagnosis is of advantage, because newly diagnosed patients are generally ART-naive. Prolonged aviremia due to long-term ART, which has been shown to lower the specificity of Inno-Lia based incident infection algorithms [18], will thus not be present. We do not recommend the Inno-Lia for IIR estimation outside of the context of prospective individual confirmation of newly diagnosed HIV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of the algorithms, Alg2 to Alg13, were published in that paper. The other 14 were developed more recently in the same way and based on the same dataset; they were used in two further studies [18], [19]. All 26 algorithms were applied to the collected Inno-Lia data of the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations